Changes in mRNA expression precede changes in microRNA expression in lesional psoriatic skin during treatment with adalimumab. (14th July 2015) - Raaby, L.; Langkilde, A.; Kjellerup, R.B.; Vinter, H.; Khatib, S.H.; Hjuler, K.F.; Johansen, C.; Iversen, L.
<x xml:space="preserve">Abstract</x> What's already known about this topic? MicroRNAs (miRNAs) are known regulators of mRNA expression and miRNA expression is altered in psoriatic skin. Tumour necrosis factor (TNF)‐α inhibitors are effective treatments for psoriasis and changes in cytokine expression profile occur in the skin after a few days of treatment. What does this study add? This study showed no change in miRNA expression after 4 days of adalimumab treatment indicating that the early cytokine changes seen in psoriatic skin during treatment are not facilitated by changes in miRNA expression. The changes in miRNA expression seen 14 days after treatment initiation is more likely a result of the improvement of the disease than of anti‐TNF‐α itself, as limited regulation was seen in the TNF‐α KO mouse.